Kinetic modeling in positron emission tomography (PET) - Kralj, Lana (Matrika, 2021)
This article firstly introduces Positron Emission Tomography (PET) as a functional and molecular imaging technique and describes main physical principles on which PET imaging works. Then, it focuses on kinetic modeling in PET. The purpose of kinetic modeling in PET is a description of radioactive tracer tissue uptake kinetics in mathematical terms. Assuming we have a mathematical model, an input function which provides the tracer concentration in blood as a function of time, and dynamic PET data which provide the tracer concentration in a tissue as a function of time, the kinetic parameters of a proposed model can be estimated. Kinetic parameters have relevant physiological interpretation, i.e provide the quantitative information about physiological processes that take place in an observed tissue or organ. Therefore, this article also introduces compartment models which are most often used method for describing the radioactive tracers tissue uptake, the concept of input function, and explaines the estimation of kinetic parameters.
Keywords: kinetic modeling; kinetično modeliranje; medical physics; medicinska fizika; positron emission tomography; pozitronska emisijska tomografija